The effect of physical activity intervention and detraining on postmenopausal osteopenia and osteoporosis: a systematic review - Gombarčíková, Tatiana; Svobodová, Lenka; Svobodová, Aneta; Gimunová, Marta (Frontiers in Sports and Active Living, 2025)
IntroductionOsteoporosis is a major health concern in postmenopausal women, and regular exercise is considered a key non-pharmacological strategy for preventing its progression. The aim of this systematic review was to evaluate the effects of physical activity and subsequent detraining on bone mineral density (BMD) in this population.MethodsThis systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Three databases (PubMed, Web of Science, and Cochrane Library) were searched. A total of 1,161 studies were identified, of which 3 met the inclusion criteria.ResultsThe findings suggest that regular resistance, aerobic, and HIIT training (2–5 sessions per week) can significantly improve or maintain BMD, particularly in the lumbar spine and proximal femur. Conversely, the cessation of exercise leads to a gradual decline in the achieved benefits within a few months.ConclusionThe results emphasize the importance of long-term physical activity as part of osteoporosis prevention while also highlighting the risks associated with the interruption of structured training.